Alamandine alleviates methotrexate-induced nephrotoxicity in rats by targeting oxidative stress and inflammation - Yildiz, Azibe; Aras, Muhammed Yasir; Gunata, Mehmet; Durhan, Merve; Polat, Seyhan; Parlakpinar, Hakan; Cigremis, Yilmaz; Vardi, Nigar (Annals of Medical Research, 2023)
Aim: Nephrotoxicity due to the use of methotrexate (Mtx) is one of the most important problems associated with chemotherapy. Oxidative stress and inflammation are the major pathomechanisms of Mtx-induced nephrotoxicity. Alamandine (Ala), a new member of the renin-angiotensin system (RAS), is an important peptide with antioxidant and anti-inflammatory capacities. In this study, it was investigated whether Ala ameliorates Mtx-induced kidney damage by reducing oxidative stress and inflammation. Materials and Methods: Male Wistar albino rats were assigned into three groups: control group, Mtx group, and Mtx+Ala group. At the end of the experiment, kidney tissues were quickly removed. Glutathione (GSH) and malondialdehyde (MDA) levels were measured to determine the oxidative state in kidney tissues. In addition, tissue samples were assessed as histopathological and immunohistochemical for heat shock protein 60 (HSP60), caspase-3, tumor necrosis factor-α (TNF-α), and receptor-interacting protein kinase-3 (RIPK3). Results: Mtx treatment resulted in reduced GSH content, elevated MDA level, increased heat shock protein 60 (HSP60), and caspase-3 expression. These changes in kidney tissues of rats treated with Mtx triggered oxidative stress characterized by apoptosis and kidney damage. Mtx also markedly increased the expression of TNF-α, an inflammation marker, and RIPK3, a marker of necroptosis. However, Ala administration significantly alleviated Mtx-induced kidney damage by reducing apoptosis and necroptosis by suppressing oxidative stress and inflammation. Conclusion: Taken together, our results support that Ala treatment can serve as a new and promising therapeutic strategy against Mtx-induced nephrotoxicity.